Pelatihan Pembuatan Studio Mini dan Teknik Digital Foto Produk Kampung Akrilik Berbasis Android - Sri Restu Ningsih Sri; Ade Irma Suryani; Rahmadini Darwas; Rahimullaily; M. Tasnim (Jurnal Abdimas Mahakam, 2023)
The problem that occurred in Acrylic Village was the craftsman's lack of knowledge about how to make a mini studio and tricks for making product photos using digital techniques. The aim of this PKM is to hold training on making mini studios and making product photos using digital techniques in Android applications. The activity implementation method includes four stages, namely: program planning, implementation, observation and evaluation. Evaluation of this activity is carried out after the activity takes place. Based on the results of the questionnaire filled out by the respondents, it was found that 87% of the members of the craftsmen did not know about mini studios and techniques for making product photos using the digital photoroom technique, and 13% stated that they already knew about this technique. For responses regarding the material presented by the resource persons it was useful for business development or adding insight, namely 89% stated it was very useful and 11% stated it was useful. The participants' responses regarding the way the resource person delivered the material, namely 73% stated it was very clear and 27% stated it was clear.